Thyroid State and Tolerance of Mammalian Myocardium to Hypoxia - Brooks, Wesley W.; Cicogna, Antonio Carlos [UNESP]; Conrad, Chester H.; Robinson, Kathleen G.; Sen, Subha; Bing, Oscar H. L. (Wiley-liss, 2009)
Thyroid hormone is known to affect myocardial glycogen stores and thereby possibly limit anaerobic performance of mammalian cardiac muscle. Thyroid hormone administration (3,5,T-triiodo-L-thyroxine, 300 mu g/kg/day, sc) for 10 days decreased left ventricle (LV) glycogen concentration relative to euthyroid animals (2.78 +/- 0.46 vs. 4.28 +/- 0.29 mg/g of LV (mean +/- SEM)) while increasing the percent of V(1) myosin isozyi-ne, contractile activity and cardiac mass. In contrast, thyroidectomy increased myocardial glycogen stores (8.50 +/- 0.56 mg/g of LV) and shifted the myosin isozyme toward V(3), prolonged contractile activity and decreased LV mass. Thyroxine administration for 3, 7 and 10 days to thyroidectomized animals progressively decreased contractile duration and increased LV mass. Thyroxine administration for 3 or 7 days to thyroidectomized rats did not reduce glycogen stores (7.75 +/- 1.02 and 9.62 +/- 1.16 mg/g of LV, respectively), whereas myocardial glycogen declined to 3.30 +/- 0.58 mg/g of LV after 10 days of treatment. During hypoxia, cardiac muscle from thyroidectomized rats maintained greater active force and developed less contracture relative to euthyroid and, to a greater extent, than hyperthyroid rats. Removal of glucose from the bath decreased anaerobic performance and impaired recovery; however, myocardium from thyroidectomized rats remained more tolerant to hypoxia than the euthyroid group. Overall, the intrinsic LV glycogen content was positively correlated to anaerobic performance. These data demonstrate that the thyroid state profoundly affects myocardial growth, contractility and anaerobic performance of rat myocardium. Although energy demand may affect function during hypoxia, anaerobic substrate reserve (cardiac glycogen concentration) appears to be the primary factor determining tolerance to hypoxic stress. J. Exp. Zool. 311A:399-407, 2009. (C) 2009 Wiley-Liss, Inc.